Analisis Persepsi Pelanggan Mengenai Kualitas Pelayanan Kesehatan Apotek Rizqi Farma Di Desa Malakasari - Ridwan Hidayat, Adris; Fitria, Ida Jalilah (STIM-LPI Makassar, 2025)
This study aims to analyze customer perceptions regarding the quality of health services at Rizqi Farma Pharmacy in Malakasari Village. The research method used is a qualitative approach. Through descriptive analysis methods, data collection was obtained through observation, interviews, and documentation studies. The results of the study indicate that most customers have a positive perception of the quality of services provided. Several key factors that are attractive include: informative consultation services, friendly and communicative attitudes from pharmacists, additional facilities such as free blood pressure checks and weighing, complete drug availability, and a clean and comfortable pharmacy environment. The most dominant indicator influencing service quality is the Tangible indicator or physical evidence facilities. However, there are still several obstacles and challenges that need to be considered during peak hours which can cause longer waiting times. Nevertheless, health services at Rizqi Farma Pharmacy continue to run optimally, and efforts to improve them are continuously being made.